Special Education Systems in Five Countries: Indonesia, Norway, Malaysia, Netherlands, Thailand - Kurniati, Dewi; Widyastono, Herry (Department of Special Education, 2020)
This article discusses a comparison of special education in five countries. Two countries are on the continent of Europe, and three other countries are on Asia's continent. This article describes the forms of special education that exist in each country. The five countries have different systems of special education policies. The similarity found from each country is that all countries have implemented an inclusive education system.